The application of collagen in the repair of peripheral nerve defect - Li, Xiaolan; Zhang, Xiang; Hao, Ming; Wang, Dongxu; Jiang, Ziping; Sun, Liqun; Gao, Yongjian; Jin, Ye; Lei, Peng; Zhuo, Yue (Frontiers in Bioengineering and Biotechnology, 2022)
Collagen is a natural polymer expressed in the extracellular matrix of the peripheral nervous system. It has become increasingly crucial in peripheral nerve reconstruction as it was involved in regulating Schwann cell behaviors, maintaining peripheral nerve functions during peripheral nerve development, and being strongly upregulated after nerve injury to promote peripheral nerve regeneration. Moreover, its biological properties, such as low immunogenicity, excellent biocompatibility, and biodegradability make it a suitable biomaterial for peripheral nerve repair. Collagen provides a suitable microenvironment to support Schwann cells’ growth, proliferation, and migration, thereby improving the regeneration and functional recovery of peripheral nerves. This review aims to summarize the characteristics of collagen as a biomaterial, analyze its role in peripheral nerve regeneration, and provide a detailed overview of the recent advances concerning the optimization of collagen nerve conduits in terms of physical properties and structure, as well as the application of the combination with the bioactive component in peripheral nerve regeneration.